2017
DOI: 10.1021/acs.jpca.7b02908
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Circular Dichroism of Transition-Metal Complexes of Perfluorophenyl-N-Confused Porphyrins: Inverting Electronic Structure through a Proton

Abstract: Neutral and deprotonated anionic Ni(II), Pd(II), Cu(II), and Cu(III) complexes of tetrakis(perfluorophenyl)-N-confused porphyrin (PF-NCP) were prepared and investigated by UV-visible and magnetic circular dichroism (MCD) spectroscopies. As in the previously reported Ni(II) adduct of tetraphenyl N-confused porphyrin, we observe sign reverse (positive to negative intensities with increasing energy) features in the MCD spectra of the neutral Ni(II), Pd(II), and Cu(II) complexes of PF-NCP, which is indicative of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 62 publications
3
16
0
Order By: Relevance
“…For instance, in the case of parent porphyrin 1 , all geometry optimizations in the gas phase and solution resulted in a stable structure of the D 4 point group with a nearly (but not exactly) planar macrocycle and phenyl groups, which were tilted from the perpendicular position by ∼20°. Such a D 4 point group geometry is in agreement with the previous reports on MTPP complexes optimized by the DFT method . When the geometry of ZnTPP 1 was forced into the D 4 h point group during geometry optimizations, the frequency calculations on converged geometries were suggestive of the transition state (negative predicted frequencies) rather than local or global minima and this was also the case for the ZINDO/1 optimized geometry of 1 .…”
Section: Results and Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For instance, in the case of parent porphyrin 1 , all geometry optimizations in the gas phase and solution resulted in a stable structure of the D 4 point group with a nearly (but not exactly) planar macrocycle and phenyl groups, which were tilted from the perpendicular position by ∼20°. Such a D 4 point group geometry is in agreement with the previous reports on MTPP complexes optimized by the DFT method . When the geometry of ZnTPP 1 was forced into the D 4 h point group during geometry optimizations, the frequency calculations on converged geometries were suggestive of the transition state (negative predicted frequencies) rather than local or global minima and this was also the case for the ZINDO/1 optimized geometry of 1 .…”
Section: Results and Discussionsupporting
confidence: 89%
“…Such a D 4 point group geometry is in agreement with the previous reports on MTPP complexes optimized by the DFT method. 67 When the geometry of ZnTPP 1 was forced into the D 4h point group during geometry optimizations, the frequency calculations on converged geometries were suggestive of the transition state (negative predicted frequencies) rather than local or global minima and this was also the case for the ZINDO/1 optimized geometry of 1. In the case of porphyrin tapes 2−12, with the DFT calculations, we found that the highest symmetry that converged to the stationary point belongs to the D 2 point group.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These two forms along with the third tautomeric 3H′‐form (three inner protons, two from sp 3 ‐CH 2 and one from NH) of NCP play an important role when complexing the metal ions inside of the core. That is, the 2H‐form and 3H′‐form serve as dianionic ligands, whereas the 3H‐form serves as a trianionic ligand (Figure b) . Although the 3H′‐form is not isolated as a genuine form but by tethering the substituent at the inner sp 3 ‐carbon atom, the dianionic coordination environment can be easily formed…”
Section: Figurementioning
confidence: 99%
“…That is, the 2H-form and 3H'-form serve as dianionic ligands, whereas the 3H-form serves as a trianionic ligand ( Figure 1b). [3,4] Although the 3H'-form is not isolated as a genuine form but by tethering the substituent at the inner sp 3carbon atom, the dianionic coordination environment can be easily formed. [5][6][7][8][9][10][11] The inner carbon atom, particularly in the form of a carbonÀ metal bond in the NCP core, is susceptible to various reactions such as alkylation, [5,6] fluoroalkylation, [7] nitration, [8] oxygenation, [9] sulfurization, [10,11] and phosphorization.…”
Section: Ruthenium N-confused Porphyrins: Selective Reactivity For Ammentioning
confidence: 99%